Sistem Informasi Akuntansi, Sistem Pengendalian Internal, Kepuasan Karyawan dan Kinerja Karyawan - Dewi, Ni Luh Dela Yunita; Kresnandra, Anak Agung Ngurah Agung (E-Jurnal Akuntansi; Vol 32 No 11 (2022)DO - 10.24843/EJA.2022.v32.i11.p13, 2022)
In the current era of globalization, the financial sector, especially Rural Banks, is experiencing intense competition which causes companies to pay more attention to the performance of their employees. The research was conducted with the aim of finding out the effect of Accounting Information Systems, Internal Control Systems and Employee Satisfaction on the Performance of BPR Employees in Tabanan Regency. The research was conducted at the BPR in Tabanan Regency, namely 270 populations with employees as samples, namely those related to finance, 72 respondents. Data obtained through questionnaires and analyzed by multiple linear regression. The research gave the results that accounting information systems, internal control systems, and employee satisfaction have a positive and significant impact on employee performance in BPR Tabanan Regency. Keywords:  Accounting Information System; Internal Control System; Employee Satisfaction; Employee Performance